2020
DOI: 10.3390/ma13183959
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Normal Force on the Tribocorrosion Behavior of a Nickel-Based Superalloy in Alkaline Solution: An Electrochemical Study

Abstract: The tribocorrosion behavior of Inconel 690TT in NaOH (pH = 9.8) solution at different normal forces was investigated by an electrochemical method. The results indicated that normal force had a great effect on the tribocorrosion behavior and mechanism. When normal force increased from 15 to 30 N, fretting regime was in gross slip regime (GSR), and wear volume gradually increased. When normal force further increased to 45 N, wear volume significantly decreased due to the fretting regime changing from GSR to part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…Long Xin studied the fretting of Inconel 690TT in NaOH (pH = 9.8) and showed that when normal force increased from 15 to 30 N, fretting was in the gross slip regime (GSR), and wear volume gradually increased [132]. When normal force increased further to 45 N, wear volume significantly decreased due to the fretting changing to the partial slip regime (PSR).…”
Section: Ph (Non-bio and Marine)mentioning
confidence: 99%
“…Long Xin studied the fretting of Inconel 690TT in NaOH (pH = 9.8) and showed that when normal force increased from 15 to 30 N, fretting was in the gross slip regime (GSR), and wear volume gradually increased [132]. When normal force increased further to 45 N, wear volume significantly decreased due to the fretting changing to the partial slip regime (PSR).…”
Section: Ph (Non-bio and Marine)mentioning
confidence: 99%